2021
DOI: 10.3390/ijms222010942
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Telocytes 16 Years on—What Have We Learned So Far, and How Close Are We to Routine Application of the Knowledge in Cardiovascular Regenerative Medicine?

Abstract: The regeneration of a diseased heart is one of the principal challenges of modern cardiovascular medicine. There has been ongoing research on stem-cell-based therapeutic approaches. A cell population called telocytes (TCs) described only 16 years ago largely contributed to the research area of cardiovascular regeneration. TCs are cells with small bodies and extremely long cytoplasmic projections called telopodes, described in all layers of the heart wall. Their functions include cell-to-cell signaling, stem-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 80 publications
(86 reference statements)
0
12
0
Order By: Relevance
“…Since the introduction of TCs/CD34 + stromal cells in the scientific literature in 2010, numerous efforts were made to inspect their existence and decipher their morphofunctional features in a variety of tissues/organs [3][4][5][6][7][8]11,12,42,43]. As a result, a growing body of evidence indicates that this long neglected, but definitely distinct, stromal cell population may greatly contribute to the shaping of the local tissue microenvironment in both health and disease [4,[6][7][8]12,[25][26][27][28]43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the introduction of TCs/CD34 + stromal cells in the scientific literature in 2010, numerous efforts were made to inspect their existence and decipher their morphofunctional features in a variety of tissues/organs [3][4][5][6][7][8]11,12,42,43]. As a result, a growing body of evidence indicates that this long neglected, but definitely distinct, stromal cell population may greatly contribute to the shaping of the local tissue microenvironment in both health and disease [4,[6][7][8]12,[25][26][27][28]43].…”
Section: Discussionmentioning
confidence: 99%
“…Since TCs are considered central regulators of the local microenvironment by communicating with many different cell types through both direct intercellular contacts and release of paracrine factors [4,6,7,32,43], a loss of the complex telopode meshwork would inevitably result in disrupted intercellular signaling and, consequently, impaired tissue homeostasis. In this regard, it is worth noting that, at variance with control mouse skin, usually fibroblasts did not appear in contact with the telopodes of TCs in the fibrotic skin of bleomycin-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…Telocytes are also found in all of the heart's layers, including the epicardium, the endocardium and the myocardium. Telocytes are found throughout the reproductive system, including the prostate, testesuterus, myometrium and placenta [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry, immunofluorescence, and scanning electron microscopy are used as auxiliary identification methods [1,2]. Importantly, TCs in the heart and blood vessels are double-positive immunostaining with CD34 and PDGFRα, including CD34 and c-kit/CD117 [5,6]. TCs are widely dispersed in various organs, especially in the heart.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…TCs are widely dispersed in various organs, especially in the heart. Furthermore, several studies and reports exist regarding cardiac TCs [5,7]. Related studies have found that cardiac TCs are in contact with almost all cells in the heart (cardiomyocytes, endothelial cells, mast cells, etc.)…”
Section: Accepted Manuscriptmentioning
confidence: 99%